2006
DOI: 10.17221/5524-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Escherichia coli, Salmonella sp. and Clostridium perfringensto organic acids and monolaurin

Abstract: The antimicrobial activity of fatty acids, monolaurin, citric, succinic, fumaric, malic and lactic acid was determined in cultures of two strains of Escherichia coli, three strains of Salmonella sp. and two strains of Clostridium perfringens. Antimicrobial activity was expressed as minimum inhibitory concentration (MIC) that prevented growth and glucose utilization in treated cultures. Caprylic acid was the only acid inhibiting glucose utilization in all cultures. Its MIC varied from 1 to 3 mg/ml. Strains CCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
135
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 21 publications
7
135
0
4
Order By: Relevance
“…There were lot published literatures to prove the inhibitory property of various MAGs against Grampositive bacteria (Kabara et al, 1972;Schlievert et al, 1992;Oh and Marshall, 1993;Branen and Davidson, 2004;Bunkova et al, 2011) and the resistant property to Gramnegative bacteria (Skrivanova et al, 2006;Kabara, 1978;Kabara, 1984). Based on detailed published studies of saturated fatty acids with chain lengths between 6 and 18 carbons, the lauric acid was found to possess more inhibitory activity against Gram-positive bacteria (Kabara et al, 1972) and MAG synthesized with caproic acid and caprylic acid in our study were found to show similar inhibitory effect.…”
Section: Anti-bacterial Effectsupporting
confidence: 61%
“…There were lot published literatures to prove the inhibitory property of various MAGs against Grampositive bacteria (Kabara et al, 1972;Schlievert et al, 1992;Oh and Marshall, 1993;Branen and Davidson, 2004;Bunkova et al, 2011) and the resistant property to Gramnegative bacteria (Skrivanova et al, 2006;Kabara, 1978;Kabara, 1984). Based on detailed published studies of saturated fatty acids with chain lengths between 6 and 18 carbons, the lauric acid was found to possess more inhibitory activity against Gram-positive bacteria (Kabara et al, 1972) and MAG synthesized with caproic acid and caprylic acid in our study were found to show similar inhibitory effect.…”
Section: Anti-bacterial Effectsupporting
confidence: 61%
“…Růžička et al (2003) did not detect an inhibitory effect of MAG-C12:0 on E. coli or Klebsiella pneumoniae. No inhibitory effect of the same MAG against Salmonella, Escherichia and Klebsiella was observed (McLay et al 2002;Marounek et al 2003;Preuss et al 2005;Skrivanova et al 2006). It was possible to enhance the antimicrobial effect of 1-monoglycerides on enterobacteria by other factors, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Under certain conditions, fatty acids and monoglycerides can inhibit the growth of vegetative forms of pathogenic bacteria, viruses (Thormar and Hilmarsson 2007), spore-forming bacteria (Mansour et al 1999;Skrivanova et al 2006) or yeasts (Bergsson et al 2001). However, food composition can influence the inhibitory effect of both monoglycerides and fatty acids.…”
mentioning
confidence: 99%
“…It has been suggested that the antimicrobial activity of medium-chain fatty acids is targeted on cell membrane, leading to disruption of electron transport chain and disruption of oxidative phosphorylation (Desbois and Smith 2010). In a study with C 2 -C 18 fatty acids caprylic acid was the most effective against Salmonella serovars and E. coli (Skřivanová et al 2006).…”
mentioning
confidence: 99%